2019
DOI: 10.1002/cbdv.201900363
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Different Parts of Saffron by Metabolomic‐Based Ultra‐Performance Liquid Chromatography Coupled with High‐Definition Mass Spectrometry

Abstract: In this study, the metabolite profiling of three different parts of Crocus sativus L. was measured by using ultra‐performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry (UPLC‐QTof‐MS/MS). Multivariate statistical analysis was used to distinguish among the samples from different parts. A total of 54 compounds were identified in tepals, stigmas and stamens by UPLC‐QTof‐MS/MS. The results stated that chemical characteristics of saffron were obviously diverse in terms of the parts of flower.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The quasi‐molecular ions of most components were (M + H) + or (M − H) − while several compounds presented more sensitivity with other adduct ions. For example, genipin 1‐gentiobioside, geniposide and crocin‐II achieved higher responses with adduct ions of (M + Na) + , which were consistent with previous studies (Xu et al, 2019; Yan et al, 2016). During the method development, we tried to change the less commonly used form of (M + Na) + to (M + H) + by adding different concentrations of acetic acid.…”
Section: Resultssupporting
confidence: 92%
“…The quasi‐molecular ions of most components were (M + H) + or (M − H) − while several compounds presented more sensitivity with other adduct ions. For example, genipin 1‐gentiobioside, geniposide and crocin‐II achieved higher responses with adduct ions of (M + Na) + , which were consistent with previous studies (Xu et al, 2019; Yan et al, 2016). During the method development, we tried to change the less commonly used form of (M + Na) + to (M + H) + by adding different concentrations of acetic acid.…”
Section: Resultssupporting
confidence: 92%
“…There are contradictory results on the detection of polymorphisms using marker-based analysis Some studies conclude that saffron is a monomorphic species and whole genome sequencing is needed to discriminate between its isolates Some studies show that molecular markers are quite efficient in detecting polymorphism. Such studies conclude that saffron is not monomorphic and that there is diversity which could be useful for breeding purposes AFLP analysis using methylation-sensitive restriction enzyme-sequencing (MRE-seq) has shown that phenotypically different but genetically similar accessions vary in the methylation pattern of genomic regions encoding transcription factors and may result in alternative phenotypes Epigenetic structure in saffron is highly stable and may play a vital role in the constancy of saffron phenotype variability ISSR primers are reported to be capable of easily distinguishing genuine saffron from fake one [44,47,47,48 H NMR-based metabolomics is useful to determine quality deterioration of saffron upon storage and for quality control Liquid chromatography coupled to electrospray ionisation time-offlight mass spectrometry is an important tool for assessing saffron authenticity Tepals may have nutrition value owing to the presence of phytosterols and fatty acids, and can be processed as a source of flavonoids Metabolite profiling of stigma, tepal and stamen of Crocus sativus flower by ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTof-MS/MS) has shown that coniferin and crocin-2 are special components in stigmas, while flavonoids are high in tepals High resolution mass spectrometry metabolomic studies in saffron from several countries has revealed that the phytochemical content varies among the samples of different countries At the yellow stage of stigma there are very low levels of crocetin, crocins, picrocrocin Picrocrocin and crocins are detected early in the orange stigma stage and increase rapidly in the red stigma stage The glycosylated products of crocetin reach maximum levels in the red stigma stage Saffron bioactive compounds are useful against coronary artery diseases, neurodegenerative disorders, bronchitis, asthma, diabetes, fever, colds, and metabolic syndrome Saffron can alleviate the symptoms of severe acute respiratory syndrome coronavirus 2 (COVID-19) patients and manage post-covid-19 syndrome The efficacy of saffron in managing depression is comparable to drugs like imipramine, fluoxetine, and citalopram Saffron can be used as an adjuvant in drug formulations as it acts as an immunity booster and anti-depressant [4,33,56,63,64,[96][97][98][99][100][101] 4. Proteomics Thirty-six differentially accumulated proteins have been detected during somatic embryogenesis in Crocus sativus and involvement of ascorbateglutathione cycle has been suspected in somatic embryo establishment Saffron protein database of stigma at different developmental stages is available through ProteomeXchange ...…”
Section: Genomics Whole Genome Sequencing Of Crocus Sp Has Not Been Donementioning
confidence: 99%
“…Recently, sensitive and high‐throughput metabolomic techniques have been widely used in the identification of active substances in medicinal plants (Li, Chen, et al, 2021; Wang et al, 2017; Xiao et al, 2015; Xu et al, 2019). In this study, we investigated the whole bioactive constitutes in the epidermis, xylem and pith of Gleditsiae Spina through ultra‐high‐performance liquid chromatography–electrospray ionization–tandem mass spectrometry (UPLC–ESI–MS/MS) analysis.…”
Section: Introductionmentioning
confidence: 99%